2016
DOI: 10.1136/gutjnl-2015-310283
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota-induced obesity requires farnesoid X receptor

Abstract: ObjectiveThe gut microbiota has been implicated as an environmental factor that modulates obesity, and recent evidence suggests that microbiota-mediated changes in bile acid profiles and signalling through the bile acid nuclear receptor farnesoid X receptor (FXR) contribute to impaired host metabolism. Here we investigated if the gut microbiota modulates obesity and associated phenotypes through FXR.DesignWe fed germ-free (GF) and conventionally raised (CONV-R) wild-type and Fxr−/− mice a high-fat diet (HFD) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
330
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 397 publications
(357 citation statements)
references
References 50 publications
3
330
0
3
Order By: Relevance
“…Interestingly, transient low-dose antibiotic treatment in early life is sufficient to evoke changes in the composition of the gut microbiota, inducing sustained effects on body composition and enhancing diet-induced obesity [35]. Colonization experiments with germ-free mouse models revealed that this host-microbiota metabolic interaction, promoting diet-induced obesity, is a transferrable trait [35,36]. In more detailed mechanistic studies with germ-free mice lacking the bile acid sensing farnesoid X nuclear receptor, signaling effects of microbiota-derived secondary bile acids were proposed as a central metabolic hub that is responsible for the contribution of gut microbiota in the development of diet-induced obesity [36,37].…”
Section: In Utero (Me Af Pl)mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, transient low-dose antibiotic treatment in early life is sufficient to evoke changes in the composition of the gut microbiota, inducing sustained effects on body composition and enhancing diet-induced obesity [35]. Colonization experiments with germ-free mouse models revealed that this host-microbiota metabolic interaction, promoting diet-induced obesity, is a transferrable trait [35,36]. In more detailed mechanistic studies with germ-free mice lacking the bile acid sensing farnesoid X nuclear receptor, signaling effects of microbiota-derived secondary bile acids were proposed as a central metabolic hub that is responsible for the contribution of gut microbiota in the development of diet-induced obesity [36,37].…”
Section: In Utero (Me Af Pl)mentioning
confidence: 99%
“…Colonization experiments with germ-free mouse models revealed that this host-microbiota metabolic interaction, promoting diet-induced obesity, is a transferrable trait [35,36]. In more detailed mechanistic studies with germ-free mice lacking the bile acid sensing farnesoid X nuclear receptor, signaling effects of microbiota-derived secondary bile acids were proposed as a central metabolic hub that is responsible for the contribution of gut microbiota in the development of diet-induced obesity [36,37]. The so far identified microbiotadriven mechanisms, contributing to obesity by modulating host energy balance, were recently reviewed [38].…”
Section: In Utero (Me Af Pl)mentioning
confidence: 99%
“…Recent evidence indicates that these changes occur in NAFLD and have potentially adverse effects on liver physiology. Altered intestinal bile acid metabolism impairs hepatic and extrahepatic signaling pathways that include the farnesoid X receptor (FXR) and the G-protein-coupled bile salt receptor TGR5, which normally mediate anti-steatotic, anti-inflammatory, and anti-fibrotic effects [65,66]. Moreover, weakening of the intestinal epithelial barrier may promote translocation of PAMPs into the portal circulation, stimulating the liver inflammatory response and disturbing sinusoidal homeostasis [48].…”
Section: Dysbiosis and The Gut-liver Axismentioning
confidence: 99%
“…Желчные кислоты могут влиять на состав микробиома как напрямую, реа-лизуя свою антимикробную функцию, так и при помощи FXR-индуцируе мой продукции антимикробных пепти-дов, таких как ангиогенин [6,7]. Исследования, прове-денные на гнотобионтных мышах дикого типа и мышах с генетическими дефектами в FXR, продемонстрировали, что изменения в составе желчных кислот, обусловлен-ные микробиотой кишечника, предрасполагают к разви-тию ожирения, НАЖБП и НАСГ [7].…”
Section: Farnesoid X Receptor (Fxr) As a Potential Therapeutic Targetunclassified